The curriculum question and school economics: Three educational scenarios for the future - Brant, Jacek Wiktor (JSSE - Journal of Social Science Education, 2022)
What shall we teach and to what end? Framing the curriculum question A ‘Future 3’ curriculum for school economics underpinned by Powerful Knowledge School economics addressing the problems faced by the world Purpose: To challenge Future 1 and Future 2 curriculum approaches and offer a more holistic vision of school economics that empowers teachers and students. Practical implications Argument for curriculum space for school economics Articulation of purpose of school economics for teachers and teacher educators Suggestion of change of didactical approach of teaching economics